Vermicompost-mediated modulation of agronomic and physiological traits enhances wheat performance under variable water regimes - Ahmad, Ali; Aslam, Zubair; Arshad, Muhammad Awais; Zulfiqar, Usman; El-Beltagi, Hossam S.; Alshaharni, Mohammed O.; Prasad, P. V. Vara (Frontiers in Sustainable Food Systems, 2025)
Wheat is a major cereal crop whose growth and productivity are highly influenced by soil moisture availability. Vermicompost application has been proposed as a sustainable approach to mitigate the adverse impacts of drought stress. This study, conducted at the University of Agriculture, Faisalabad, during 2020–2021 and 2021–2022, investigated the effects of different vermicompost sources on agronomic, physiological, and nutrient traits of wheat under varying soil moisture regimes. The experiment included three soil moisture levels (no drought, mild drought, and severe drought), four vermicompost (VT) levels (control, 8 t ha−1 wheat straw vermicompost, 6 t ha−1 rice straw vermicompost, and 6 t ha−1 cow dung vermicompost), and two wheat cultivars: Faisalabad-08 (drought-tolerant) and Galaxy-13 (drought-sensitive). Results revealed that drought stress significantly reduced growth, yield, and physiological attributes. However, vermicompost application alleviated these effects, with cow dung vermicompost showing the greatest improvement, followed by rice straw and wheat straw vermicompost. Furthermore, Faisalabad-08 performed better than Galaxy-13 under both mild and severe drought conditions. Overall, the findings highlight that applying vermicompost, particularly from cow dung, to the soil is an effective strategy to improve wheat resilience and productivity under drought stress.